2020
DOI: 10.33258/birci.v3i4.1456
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and Function of Local Wisdom in the Proverb (Limbaga) Simalungun

Abstract: Aims to describe the meaning and function of local wisdom contained in proverbs or called limbaga Simalungun. The meaning and function of local wisdom is a general guideline or principle adopted by every member of society, especially in attitude and behavior, to meet social needs. Therefore, value is an idea related to what is considered good, worthy and desired by all levels of society in life. The data collection method used in this study is a descriptive qualitative method which tends to use analysis. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
0
0
1
Order By: Relevance
“…Bersumberkan pada KBBI atau Kamus Besar Bahasa Indonesia, kearifan memiliki makna kecendekiaan kebijaksanaan, menjadi sesuatu yang diperlukan untuk melakukan interaksi. Kearifan lokal merupakan suatu pengetahuan asli dalam satuan masyarakat yang berasal dari tradisi turun-temurun yang pada akhirnya melahirkan pola kehidupan masyarakat setempat (Purba & Siahaan, 2020). Pada UU No.…”
Section: Hasil Dan Pembahasan Kearifan Lokalunclassified
“…Bersumberkan pada KBBI atau Kamus Besar Bahasa Indonesia, kearifan memiliki makna kecendekiaan kebijaksanaan, menjadi sesuatu yang diperlukan untuk melakukan interaksi. Kearifan lokal merupakan suatu pengetahuan asli dalam satuan masyarakat yang berasal dari tradisi turun-temurun yang pada akhirnya melahirkan pola kehidupan masyarakat setempat (Purba & Siahaan, 2020). Pada UU No.…”
Section: Hasil Dan Pembahasan Kearifan Lokalunclassified
“…The local wisdom of nuwo stilts has played an influential role in mitigating and reducing the risk of flood disasters, namely as an evacuation site for residents who do not have stilt houses and a place to secure the residents' valuables. Local wisdom that residents maintain is learned from nature by considering everything that is good and useful so that local wisdom, which was initially a culture and inherited values, can become something that residents utilize, including in disaster management (Purba et al, 2020). Law Number 24 of 2007 concerning disaster management instructs that the purpose of disaster management is not only to provide protection to residents from disaster threats but also to pay attention to the appreciation of local culture so that it can be concluded that disaster management efforts cannot be separated from local wisdom (Alexandra et al, 2019).…”
Section: B 2 Nuwo Panggung Local Wisdom In Flood Disaster Managementmentioning
confidence: 99%
“…These values are commonly referred to as local wisdom. Values are concepts that are considered good or worthy by a particular community, originating from the shared beliefs of that community (Purba et al, 2020). Hence, the manifestation of cultural activities among different societies varies, depending on the consensus among the members of the community.…”
Section: Local Wisdommentioning
confidence: 99%
“…Local wisdom is a type of knowledge that results from the crystallization of noble values within a community, which help regulate life in that community (Hunaepi & Firdaus, 2017;Naryatmojo, 2019;Purba et al, 2020;Sembiring et al, 2019). According to Pesurnay (2018), local wisdom is a social-communicative system within a culture that results in self-organization.…”
Section: Local Wisdommentioning
confidence: 99%